HUBUNGAN ASUPAN MAKRONUTRIEN, INDEKS MASSA TUBUH (IMT) DAN AKTIVITAS FISIK DENGAN KESEGARAN JASMANI PADA LANSIA (Studi di Posyandu Lansia Bumi Asri RW IV Kelurahan Sambiroto, Kecamatan Tembalang, Semarang Tahun 2018) - Camelia Nurjannah; M. Zen Rahfiludin; Apoina Kartini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Physical fitness is one of the public health indicators in the elderly. Physical fitness in elderly has factors related to adequate nutritional fulfillment. The purpose of this study was to analyze the correlation between macronutrient intake, body mass index and physical activity with physical fitness in elderly. This quantitative observational study used a cross sectional design. Fortythree subjects were selected by using consecutive sampling technique based on (60 – 74) age and being active as members of the Posyandu Lansia Bumi Asri in a certain period of time. Physical fitness measurements were carried out based on the results of the Six Minutes Walk Test. Measurement of intake used Estimated Food Records. Data analysis used Rank - Spearman test. The results showed that the respondents had a mean BMI of 25.06 ± 3.73 kg / m2 and physical activity was 1.4 ± 0.08 PAL. The elderly have a mean physical fitness of 293 ± 49 meters and the average level of energy adequacy was (77.95 ± 12.93)% and the mean level of protein adequacy was (74.44 ± 13.91)%. There were correlations between the level of protein adequacy (r = - 0.458 p = 0.002) and  physical activity (r = 0.652 p = 0.0001) with physical fitness, but there were no correlations between the level of energy adequacy (r = -0.143 p = 0.361),  BMI in the thin and normal category (r = 0.201 p = 0.369), BMI in the fat category and obesity (r = 0.075 p = 0.748) with the physical fitness. In brief, there were correlations between protein intake and physical activity with physical fitness in elderly.